THE USE OF THEN IN LITHUANIAN LEARNERS’ ENGLISH - Bikelienė, Lina (Verbum, 2018)
In linguistic literature, learner language has been extensively analysed from various perspectives. A number of studies have reported on the differences between non-native and native learner English. The former has been repeatedly characterised as showing the overuse of the features associated with spoken English (Gilquin and Paquot 2007, 2008; Russell 2014; Yoon 2015). Though in linguistic analysis, due to its polyfunctional nature, ‘then’ has been addressed under a number of various labels, from the quantitative perspective it is reported to be characteristic of spoken English (Biber et al. 1999). The present study, limited to the analysis of non-native language data, aims at determining the roles of language mode and text genre on the use of ‘then’ in the Lithuanian learners’ English. Using quantitative and qualitative approaches three corpora representing the spoken (LINDSEI-LIT) and written (LICLE-VU-LIT and CALE-LIT) English produced by the Lithuanian students were analysed. While the results indicate a direct correlation between language mode and the use of ‘then’, the role of genre proved to be less unequivocal.
Keywords: learner language; language mode variable; language genre variable